Оптимізація втрат в управлінні інформаційними витратами переробного підприємства - Замула, Олена Василівна (ВД "ІНЖЕК", 2015)
Мета статті полягає в дослідженні інформаційних втрат як економічної категорії та пошук моделі, що дозволить зменшити їх рівень до мінімального. Аналіз літературних джерел з цієї проблематики показав, що науковці більше переймаються втратами, що пов’язані з ризиками функціонування інформаційної системи, коли носіями інформації є технічні пристрої, хоча значну частину роботи з одержання, обробки, захисту та розповсюдження інформації здійснює персонал підприємства чи сторонні організації (у разі застосування аутсорсингу).

The article is aimed at studying the information losses as an economic category and searching the model, which will help to reduce their level to a minimum. Analysis of literature on the subject has shown that scientists are more concerned about losses relating to risks related to function of information system, where the media are technical devices, although much of the work to receive, process, and distribute information is carried out by staff of the enterprise or by third parties (in the case of using the outsourcing). During the study the notion of "information losses" has been determined as decrease of information asset without adding the end product value, or reduce of the professional level of staff, due to intentional or unforeseen events. Information risks and the losses associated with them can be divided into transformational, where information is available within the enterprise for own use or for sale, and transactional, which most often arise in case when executives prefer to buy products and services of the information market, taking advantage of the benefits of outsourcing. Losses can be significant because of the hidden actions of economic agents and the related moral hazard, high probability of adverse selection and corruption, therefore has been proposed to minimize them through finding the optimum ratio of insourcing and outsourcing information costs, as well as formation and appropriate filling of information infrastructure. As to further researches it will be interesting to study the human factor in occurrence of information risks under the current institutional environment and to find ways to reduce them by forming the appropriate corporate culture.
Optimizing Losses in the Management of Information Expences of Processing Enterprise
Keywords: інформаційний ризик; втрати; аутсорсинг; захист інформації; інформаційна інфраструктура; information risk; losses; outsourcing; information security; information infrastructure